The Concept of Economic Evaluation and Its Application in Thyroid Cancer Research - Kim, Kyungsik; Kim, Mijin; Lim, Woojin; Kim, Bo Hyun; Park, Sue K. (Endocrinology and metabolism (Seoul), 2021)
Economic evaluation is a type of comparative analysis between interventions in terms of both their resource use and health outcomes. Due to the good prognosis of thyroid cancer (TC), the socioeconomic burden of TC patients post-diagnosis is increasing. Therefore, economic evaluation studies focusing on TC are recommended. This study aimed to describe the concept and methods of economic evaluation and reviewed previous TC studies. Several previous studies compared the costs of interventions or evaluated recurrence, complications, or quality of life as measures of their effectiveness. Regarding costs, most studies focused on direct costs and applied hypothetical models. Cost-minimization analysis should be distinguished from simple cost analysis. Furthermore, due to the universality of the term “cost-effectiveness analysis” (CEA), several studies have not distinguished CEA from cost-utility analysis; this point needs to be considered in future research. Cost-benefit analyses have not been conducted in previous TC research. Since TC has a high survival rate and good prognosis, the need for economic evaluations has recently been pointed out. Therefore, correct concepts and methods are needed to obtain clear economic evaluation results. On this basis, it will be possible to provide appropriate guidelines for TC treatment and management in the future.